Compensatory Ethics - Zhong, Chen-Bo (Journal of business ethics, 2010)
Several theories, both ancient and recent, suggest that having the time to contemplate a decision should increase moral awareness and the likelihood of ethical choices. Our findings indicated just the opposite: greater time for deliberation led to less ethical decisions. Post-hoc analyses and a followup experiment suggested that decision makers act as if their previous choices have created or lost moral credentials: after an ethical first choice, people acted significantly less ethically in their subsequent choice but after an unethical first choice, people acted significantly more ethically in their subsequent choice. These findings provide the basis for a model of compensatory ethics.